Soil percolation and efficacy of fungicides on the inoculum of Phytophthora palmivora MF4 , the incitant of black pepper wilt - R. K. HEGDE*, M. N. L. SASTRY and (Indian Phytopathology, 2002)
The percolation studies with different fungicides on their ability to check the soil-borne inoculum of Phytophthora palmivora MF4 , the incitant to black pepper wilt, revealed that drenching of terrazole (1000 ppm) had a total inhibitory effect on the inoculum present up to a depth of 2.5 cm. Dexon and metalaxyl (both at 1000 ppm) drenches had total inhibitory effect on the inoculum present upto a depth of 1.25 cm only. Bordeaux mixture (at both 0.5 and I per cent concentrations) was least percolative. In all the above treatments, it was recorded that as the depth at which the inoculum present increases the effect of fungicides on P. palmivora inoculum decreases.